Literature Review of Water Alternation Gas Injection - mohammed Alsharif Samba (Journal of Earth Energy Engineering, 2018)
The Water Alternating Gas (WAG) process is a cyclic method of injecting alternating cycles of gas followed by water and repeating this process over a number of cycles. WAG injection is to improve oil recovery, by both increasing the macroscopic and microscopic sweep efficiency and to help maintain the reservoir pressure. Also, WAG injection is to postpone the gas breakthrough. The WAG process provides mobility control in fast zones which extends gas project life and oil recovery. This paper provided a comprehensive literature study about WAG injection. This paper has collected most of the requirements of the petroleum engineers that has to know about the WAG injection started from basic concepts until the design parameter for WAG injection.